Sistem Penjualan Merchandise Berbasis Aplikasi Mobile - Wijaya, Partha; Widiartha, I Made (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023, 2023)
The rapid growth of mobile technology has revolutionized various industries, including merchandise sales. This paper presents a study on the development of a mobile application-based merchandise sales system aimed at replacing manual recording reports by merchandisers and expanding the range of reportable data. By harnessing the capabilities of mobile devices, the research focuses on analyzing merchandisers' requirements and designing user-friendly interfaces. Through thorough testing and evaluation, the system showcases its reliability and functionality. This study contributes to the existing body of knowledge by offering valuable insights into the advantages and challenges of adopting mobile technology in merchandise sales.